Prison and social death - Price, Joshua M. (Critical issues in crime and society., 2015)
The United States imprisons more of its citizens than any other nation in the world. To be sentenced to prison is to face systematic violence, humiliation, and, perhaps worst of all, separation from family and community. It is, to borrow Orlando Patterson's term, to suffer "social death." In Prison and Social Death, Joshua Price exposes the unexamined cost that prisoners pay while incarcerated and after release, drawing upon hundreds of often harrowing interviews conducted with people in prison, people on parole, and their families. Price argues that the prison separates incarcerated people from desperately needed communities of support and that this isolation of people in prison renders them highly vulnerable to other forms of violence, including sexual violence. Price stresses that the violence they face also involves institutional forms of mistreatment, ranging from abysmally poor health care to routine practices that are arguably abusive. And social death does not end with prison. The condition is permanent, following people after they are released from prison.